THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE ENGAGEMENT - Manmeet Kaur, Jaswant Singh; Poh, Phaik See (INTI International University, 2022)
Organisations and leaders seek to have engaged employees and spend considerable time and resources to improve engagement which has enormous influence on employee productivity and organisational performance. Although there have been previous studies in Malaysia, little research has been done on leadership’s influence on employee engagement across industries. Transformational and transactional leadership is stated to be positively correlated with employee motivation and employee satisfaction, and indirectly employee engagement. This study examines the leadership style practised by leaders in five organisations in Malaysia, its influence on employee motivation and satisfaction which lead to an increase or decrease in employee engagement. Data on leadership style, employee motivation, satisfaction and engagement, and organisational culture was gathered through a web based questionnaire from employees. Quantitative data from leaders on their leadership style, motivation, satisfaction, engagement whereas those on organisational culture was gathered qualitatively. Responses from the web based employee questionnaire were processed using IBM’s Statistical Package for the Social Sciences (SPSS) 22. The qualitative data gathered from leaders were processed via the in vivo technique, clustered and classified into patterns according to the emerging common themes using Microsoft Excel, together with quantitative data. The findings of the study show that transformational and transactional leadership style influences employee satisfaction more than employee motivation, which impacts employee engagement. Employees led by transformational leaders have the highest satisfaction levels with their job, leadership style and organisation whereas teamwork outshines while working with a transactional leader. Finally, in project-related industries, the laissez-faire leadership style is prominent as in encouraging employee empowerment and autonomy in decision making which ultimately results in higher employee engagement. Sub-unit culture rather than organisational culture has a moderating influence on the relationship between leadership style and employee engagement.